Lipid chain oxidation promotes binding of acute-phase C-Reactive protein to cell membranes - Weißenfeld, Felix; Nagai, Shogo; Kröll, Alexander; Yamamoto, Akihisa; Abuillan, Wasim; Korytowski, Agatha Anna; Kaufmann, Stefan; Tanaka, Motomu (Langmuir, 2025)
C-reactive protein (CRP) is a homopentameric, acute-phase inflammatory protein, whose level in serum is widely used as a biomarker for detecting inflammation, injury, and infection. In the presence of Ca2+ ions, CRP binds to oxidized lipids and lipoproteins with phosphatidylcholine (PC) head groups present on apoptotic cells and initiates the complement pathway of innate immunity. It has been reported that CRP does not bind to PC membranes in the absence of oxidized PC (OxPC). To unravel how CRP-membrane interactions are affected by OxPC, we incorporated two different oxidative products, possessing aldehyde and carboxylate moieties, into the vesicles of PC lipids and monitored the CRP-vesicle interactions. Using dynamic light scattering, we found that the CRP induced the fusion of vesicles containing OxPC. The fusion occurred at around the same CRP concentration (0.5-0.8 μM), but the kinetics was faster for carboxylated lipids. In contrast, vesicles of nonoxidized PC remained intact. Fourier analysis of membrane fluctuation indicated that the membrane containing OxPC is much softer than that of nonoxidized control, which agrees well with the decrease in the lateral chain packing and the membrane thinning suggested by the previous studies. Intriguingly, CRP showed a higher affinity to vesicles containing OxPC in a Ca2+-dependent manner. As the previous study showed the condensation of Ca2+ near the oxidized membrane surface, we concluded that CRP is recruited to the surface of an OxPC-containing, poorly packed membrane enriched with Ca2+, resulting in the stiffening of apoptotic cell membranes.